Rare Head and Neck Benign Mesenchymoma in Close Proximity to Submandibular Gland in a Pediatric Patient: Case Report and Review of the Literature - Priyanka Jain; Shraddha Mukerji (Case Reports in Otolaryngology)
Pediatric head and neck masses are commonly congenital in origin or of infectious etiology. We present a rare case of benign mesenchymoma in close proximity to the submandibular gland in an otherwise asymptomatic child. Computerized tomography (CT) scan of the head and neck area revealed a benign lesion, which was later determined to be a benign mesenchymoma on histopathology. The child did well after surgery without any reported recurrence. We discuss the salient features of a benign mesenchymoma in a child and also discuss relevant imaging and management.